Cardiac biomarkers in acute coronary syndromes - Ranjith, Naresh; Naidoo, Datshana P. (SA Heart Journal, 2017)
Cardiac biomarkers play a significant role in the diagnosis, risk assessment, and management of patients with acute coronary syndromes (ACS). Several biomarkers identify different components of the pathophysiology of ACS: troponins are markers of myocyte necrosis, natriuretic peptides reflect neurohormonal activation and myocardial dysfunction, and C-reactive protein reflects various inflammatory processes. Whilst there are a number of established and novel biomarkers to assess ischemia, necrosis and myocardial dysfunction in coronary artery disease, it is probable that no single biomarker will emerge that provides appropriate information for all clinical settings of ACS. This suggests that ongoing efforts in plasma-based biomarker research should concentrate on the use of a multimarker approach to enhance our diagnosis, prognostic assessment, and management of patients with suspected ACS, as compared with using individual markers alone. It is recommended that current practice involve the selective use of biomarkers in patients in whom a more complete assessment of risk is desired. At present, routine biomarker measurement is not advocated until further data become available, which will support the benefit of specific therapeutic interventions.